Applications of Finite Element Modeling in Biomechanical Analysis of Foot Arch Deformation: A Scoping Review - Cen, Xuanzhen; Song, Yang; Sun, Dong; Bíró, István; Gu, Yaodong (Journal of biomechanical engineering, 2023)
Excessive foot arch deformation is associated with plantar tissue overload and ligamentous injury pathologies. Finite element (FE) analysis, as an effective tool for modeling and simulation, has been utilized clinically for providing insights into arch biomechanics. This systematic scoping review aimed to summarize the current state of computational modeling techniques utilized in arch biomechanics from 2000 onwards and outline the main challenges confronting the further development of accurate models in clinical conditions. English-language searches of the electronic databases were conducted in the Web of Science, PubMed, and Scopus until July 2022. Articles that investigated arch deformation mechanisms by FE modeling were included. The methodological quality was assessed utilizing the Methodological Quality Assessment of Subject-Specific Finite Element Analysis Used in Computational Orthopedics (MQSSFE). Seventeen articles were identified in this systematic scoping review, mostly focusing on constructing models for specific pathological conditions, such as progressive collapsing foot deformity, valgus foot, and posterior tibial tendon dysfunction. However, given the complexity of the arch problem, geometrical simplifications regarding the balance between accurate detail and computational cost and assumptions made in defining modeling parameters (material properties and loading and boundary conditions) may bring challenges to the accuracy and generalizability of models applied to clinical settings. Overall, advances in computational modeling techniques have contributed to reliable foot deformation simulation and analysis in modern personalized medicine.